GREEN ACCOUNTING, ECO-EFFICIENCY, AND CORPORATE FINANCIAL PERFORMANCE - Indi Rahma; Sigit Mareta; Caturida Meiwanto Doktoralina; Natalia Santoso; Ahmad Badawi (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study to analyze the relationship between Green Accounting, Eco Efficiency and Carbon Emission Disclosure to financial performance. This study uses a quantitative approach with secondary data analysis taken form the annual reports of companies listed on the Indonesia Stock Exchange (IDX). This study examines the relationship between independent variables, namely Green Accounting, Eco Efficiency and Carbon Emission Disclosure with the dependent variable, namely Financial Performance. This approach allows researchers to identify significant patterns confirm and relationships between environmentally friendly practice and company financial results. These findings confirm that transparency in carbon emission disclosure can increase investor confidence and contribute to better financial performance. This study provides originality regarding Green Accounting and Financial Performance in Indonesia, and provides empirical evidence supporting the importance of carbon emission disclosure in increasing transparency and investor confidence. This study not only highlights the importance of implementing environmentally friendly practices, but also encourages cross-sector collaboration to achieve better sustainability and energy efficiency goals.